Breaking policy silos for sustainable development: A report on policy coherence in India's food, land and water sectors - Taneja, Garima; Mitra, Archisman; Katyaini, Suparana; Bhattacharjee, Suchiradipta (CGIAR System Organization, 2024)
Policies in the food, land, and water sectors are intricately connected, as they interact and mutually influence each other at the operational level, ultimately shaping their overall effectiveness. Policies within one sector can encounter obstacles from divergent policies in other sectors. Therefore, it is important to coordinate and ensure that related policies share common goals, while also identifying any potential contradictions between them. The need for policy coherence is particularly significant for a vast and diverse country like India. However, policies are often developed in silos, leading to unintended consequences, duplication, fragmentation, and reduced efficiency in resource use. Over time, there has been an increasing recognition of the importance of analyzing policies through the lens of policy coherence and conducting research on fostering synergies and drafting policies that are mutually reinforcing rather than divergent.